DISTANCE LEARNING AND COVID-19 FROM STUDENTS’ PERSPECTIVE: DO THEY HAVE THE SKILLS TO DEAL WITH THE UNPRECEDENTED SITUATION? - Hačatrjana, Liena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
As a result of the COVID-19 pandemic, more than 1,6 billion children worldwide were forced to discontinue face-to-face education and continue with distance learning (OECD, 2020). To many students as well as teachers this was their first experience with distance learning. Students' ability to adapt to distance learning varies and depends on different factors, including individual factors such as the ability to cope with new situations, solve problems and manage their own learning process. In order to successfully deal with the new circumstances in education, it is necessary to work at all levels - including the level of policy development, level of schools as organizations, and at the individual – the student – level. This article focus on the level of the students and look on the distance learning from the perspective of students’ skills, attitudes and ability to adapt to the situation. The aim of this article is to summarize what has been studied so far in different countries about COVID-19 related distance learning and students' difficulties and ability to cope with this situation; and to suggest practices to develop students' skills such as self-management and problem-solving skills to better adapt to new situations in the future.